Implementasi sistem informasi persediaan barang untuk mengurangi kesalahan pencatatan - Carolyn Christian; Hadisantono; Theodorus B. Hanandoko; Parama Kartika Dewa (Universitas Atma Jaya Yogyakarta, 2026)
[Implementation of an inventory information system to reduce recording errors] The material warehouse plays a crucial role in supporting the company's production process, storing raw materials and finished products. Raw material inventory is key to the production process, and the quality and quantity of incoming and outgoing goods must be controlled. PT JGI (Jogja Glove Indonesia) implements manual inventory recording using Microsoft Excel, but its implementation is less than optimal. The company's problem is errors in recording incoming and outgoing goods in the material warehouse, resulting in discrepancies between actual data and the book data. The average number of recording errors is 12 times of month. This problem was resolved because it resulted in inconsistencies in raw material inventory, thus hampering the production process. The solution provided to overcome this problem is to create an information system with VBA Excel for recording goods and SOP (Standard Operating Procedures) for goods entering the warehouse. The method used to create the information system and SOP is the SDLC (System Development Life Cycle) method for information systems and the PDCA (Plan, Do, Check, Action) method for creating SOP. The results of the information system design and SOP that have been implemented have been proven to be successful in overcoming the root cause of errors in recording goods, so that the frequency of recording errors can be reduced from 12 times of month to 3 times of month.